2021
DOI: 10.2217/fon-2021-0588
|View full text |Cite
|
Sign up to set email alerts
|

Real-world use of bevacizumab-awwb, a bevacizumab biosimilar, in US patients with metastatic colorectal cancer

Abstract: Aim: Evaluated real world use of bevacizumab-awwb (MVASI®), a bevacizumab biosimilar, for treating metastatic colorectal cancer (mCRC). Materials & methods: Adult mCRC patients who received bevacizumab-awwb during the first year after market availability were identified from the ConcertAI oncology dataset. Results: Of 304 patients, 47% initiated bevacizumab-awwb as reference product (RP) naive patients and 53% received bevacizumab-awwb with prior exposure to RP. Overall, 78% received bevacizumab-awwb as fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Missing data were not imputed and were reported as 'undocumented' or 'unknown.' 29 PFS and OS probability and time to event outcomes, along with their associated 95% confidence intervals (CIs), were analyzed using Kaplan-Meier curves. The incidence at which each EOI occurred was described at patient level according to the management action(s) for the EOI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Missing data were not imputed and were reported as 'undocumented' or 'unknown.' 29 PFS and OS probability and time to event outcomes, along with their associated 95% confidence intervals (CIs), were analyzed using Kaplan-Meier curves. The incidence at which each EOI occurred was described at patient level according to the management action(s) for the EOI.…”
Section: Discussionmentioning
confidence: 99%
“…2932 Patient baseline characteristics were abstracted from unstructured EMRs by trained clinical research nurses and linked to patient data extracted from standard fields as described previously. 29 Treatment patterns of bevacizumab-awwb were collected, including durations of 1L bevacizumab-awwb use, prior treatment history of RP, and other systemic anticancer therapy (chemotherapy or immunotherapy). The occurrence and date of disease progression were determined from pathology reports, radiological scan notes, and/or statements about disease progression in oncologist progress notes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective, real-world study which had enrolled a total of 304 patients diagnosed with mCRC who initiated MVASI as rst-or later-line treatment, demonstrated that most patients (83%) experienced no disease progression between their last treatment with the reference product and the starting of treatment with a bevacizumab biosimilar [35] .…”
Section: Treatment Patterns and Clinical Outcomesmentioning
confidence: 99%